Providing a business model for massive open online courses (MOOCs) in Iran - Milad Rasekh; Mahmood Eghtesadifard; Mohammad Hossein Ronaghi; Abolghasem Ebrahimi (کاوش‌های مدیریت بازرگانی, 2022)
Introduction: Massive open online courses (MOOCs) are known as new advances in e-learning. Learning through MOOCs requires different education than what happens in face-to-face learning. In these courses, it is important to connect with participants from different backgrounds and personalize learning. Therefore, with the development of MOOC as a new teaching method, training-based businesses need to acquire new knowledge and skills to obtain the desired training and gain acceptable learning outcomes. An important aspect of innovation in this business is tied to the role of the Internet and the related technologies, but this feature is not necessarily the only aspect that leads to innovation in the MOOC business model. This is because, with the advent of these technologies, there has been a significant shift in attitudes towards training and skill development systems that have changed the education business environment. Besides, the characteristics of this business are different from those of other web-based businesses which require that a business model be provided specifically for MOOC. The business model explains the logic of an organization on how to create, deliver, and acquire values. Thus, the business model helps to understand the relevant factors in the business context and to recognize and interact with them. In this environment, business logic is constantly changing and improving. A business model can integrate resources, activities and knowledge and facilitate the identification of competency resources. The model also helps businesses to fulfil their mission and reduce budgetary and financial pressures and constraints. Despite the increased number of MOOCs in Iran, some entrepreneurs have failed due to several factors, including the weakness of these institutions to adapting to environmental conditions and their changes as well as the weakness of their commercialization strategy. Therefore, setting up MOOC courses requires structures and resources that must be identified in interactions with the business environment before any action is taken. A business model can identify the important components of creating a competitive advantage in accordance with environmental factors and promote the development of businesses based on economic principles as well as educational policies. Accordingly, this paper aimed to provide a business model in line with the features of the MOOC that can specify important business components and develop a business strategy in accordance with educational policies.Methodology: In this study, the mixed research method has been used to create comprehensible designs from the analysis of complex data. This method is a process for collecting, analyzing and describing qualitative and quantitative data that help to better understand the challenges of research. Using only a qualitative or quantitative research approach reveals only a few aspects of the phenomenon being studied. Therefore, the mixed research method provides a better understanding of various phenomena. This research is based on a mixed approach, qualitative and quantitative, in two stages. In the qualitative phase, a systematic review approach has been used to identify the components of the e-business model. Then, experts' opinions are used to match the components of the e-business model (obtained from systematic review) with the characteristics of the MOOC business model and to reach the proposed components for the MOOC business model. In the quantitative phase, a questionnaire has been prepared and provided to the experts to evaluate the proposed components for the MOOC business model. The t-test serves to analyze the answers and finalize the components of the model, and the Friedman test prioritizes the components. In the second stage, the fuzzy Delphi approach is used to present the MOOC business model.Results and Discussion: The elements of the MOOC model proposed in this study are highly consistent with a business model. In a sense, the components of the MOOC model project the aspects of a business model in more details. The sub-components in the model address features that are specific to MOOC businesses and, therefore, do not apply to other types of e-businesses in general. To develop the model, the opinions of MOOC business experts and entrepreneurs were taken into consideration, which could be fruitful to improve MOOC implementation plans in Iran as well as its competitive position.Conclusion: According to the findings of this research, the model of earnings, the proposed value and the customer are the most important components of a MOOC business model. It is presented in the form of 55 concepts in 12 main components. The use of the proposed model has such benefits as promoting MOOC planning and facilitating the acquisition of competitive advantage. Besides, the results of this study can be used by entrepreneurs in this field to create successful business models. The insight provided by this study can lead to a common understanding among e-learning activists about the challenges in the MOOC business. Due to technological innovations, it also lays the ground for future changes in the field.